Polimorfismo G22A do gene ADA e abortamento espontâneo recorrente: ausência de associação - Nunes, Daniela Prudente Teixeira (2010)
Adenosine deaminase (ADA), an enzyme coded by ADA gene (20q13.11) acts in adenosine metabolism and it is involved in the modulation of the immune response. ADA gene G22A polymorphism originates two co-dominants alleles ADA*01 and ADA*02 and influences the level of ADA enzyme in the organism. Apparently it has a fundamental role in gestational maintenance. The ADA*02 allele has been associated as protector effect against recurrent spontaneous abortion (RSA) in European Caucasian women. Aim: To investigate if ADA gene G22A polymorphism is associated with occurrence of RSA in Brazilian women. Methods: After obtaining the written consent 311 women were selected to compose two groups: G1 with previous history of RSA (n=129) and G2 without previous history of RSA (n=182). Genomic DNA was isolated from peripheral blood using commercial kits. The PCR-RFLP method was used to identify ADA gene G22A polymorphism. p>0005 was considered statistically significant. Results: The frequencies of ADA*01;*01, ADA*01;*02 and ADA*02;*02 genotypes were similar in both groups (G1 and G2) with no statistically significance differences observed (p = 0,7170; x2 = 0,6653; GL = 2). ADA*01 and ADA*02 alleles frequencies were 95,6% and 4,4% in G1 group and 94,9% and 5,1% in G2 group, respectively (p = 0,8433; OR = 1,179; CI 95%: 0,5340 2.601). Conclusion: The results suggest that ADA alleles ADA*01 and ADA*02 are not associated with RSA. It xvi is possible that the reduction of ADA levels resulting from the presence of at least one ADA*02 allele do not have a role against abortion in Brazilian women.